Política de formação docente e ferramentas digitais em tempos pandêmicos: desafios e possibilidades - Santos, Rodrigo de Oliveira (2024)
This research proposed to analyze the teacher training policies in the context of the pandemic in the final years of elementary school in the municipality of João Pessoa, PB. The pandemic context brought imperatives, psychological, emotional and formative challenges to the entire school community. In light of this, social distancing and remote learning have become ways to minimize the spread of the virus and the alternative of continuing the school year. In this sense, with the transfer of teaching to the virtual environment, teachers were faced with a new reality that demanded new attitudes from them pedagogical. From there, remote teaching was anchored in digital tools as a way to try to overcome the challenges posed. In addition to these initial elements presented, what were the teacher training policies for remote teaching during the pandemic in the years Elementary school finals in the municipality of João Pessoa – PB? Based on this problem, it is possible to perceive a fragmentation in the training policies for action of remote education, because each municipality and state developed its own training policy, since the federal government took a long time to direct this emergency policy. To support the teacher training policy, the following we use: (Albino; Silva, 2019); (Bezerra; Silva; Albino, 2021); (Rocha; Pereira, 2019), to support digital technologies, it was used (Adão, 2023). Our research was based on a qualitative approach to support digital technologies, it was used (Adão, 2023); Hobold; Mattos (2010); (Costa; Oliveira, 2015). Our research was based on a qualitative approach as a procedure, the case study (Yin, 1994; 2010) was used to understand the complex and atypical context that was the pandemic. In addition to Yin, the following were used in the technical procedures: bibliographic and documentary research that subsidized our analyses from the normative point of view (Cellard, 2008); (Richardson, 2017). The legal documents that constituted and supported this research were: the (BNC-F, 2019) and Decree No. 5/2020. For our theoreticalmethodological framework, the Policy Cycle Approach was used Ball; Gold, 1992); (Ball; Maguire; Braun, 2021). For this research, we used the context of text production with normative and legal bases and the context of practice, where the interpretation and recreation of policies take place. To collect the data, the questionnaire (Gill, 1999) was used as a tool that gathered information about the teachers. For data analysis, the research is based on: (Gestrado, 2020); (Cordeiro, 2020); Galzerano, 2021); (Hobold; Mattos, 2010), these authors brought elements that problematize the emergency policies that emerged during the pandemic. During the pandemic, it is clear that policies revolved around the reorganization and continuity of the school calendar. Furthermore, it is observed that the implications of the pandemic hit education hard and, consequently, the poorest layers. Under the maxim that “Education cannot stop”, teachers and students were thrown into a reality surrounded by difficulties, disagreements and hostility. For many students, remote teaching was nothing more than a fallacy, as the majority did not have the equipment, subjective conditions or objective conditions to participate in emergency remote teaching. Finally, the school community, in an abrupt and ephemeral way, had its reality changed, while they had to deal with the imperatives of the pandemic (social, economic and technological inequalities), the global crisis, capital and the advancement of the neoliberal perspective On education.